2009
DOI: 10.1073/pnas.0902230106
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatase activity in the neural crest is essential for normal heart and skull development

Abstract: Mutations within the protein tyrosine phosphatase, SHP2, which is encoded by PTPN11, cause a significant proportion of Noonan syndrome (NS) cases, typically presenting with both cardiac disease and craniofacial abnormalities. Neural crest cells (NCCs) participate in both heart and skull formation, but the role of SHP2 signaling in NCC has not yet been determined. To gain insight into the role of SHP2 in NCC function, we ablated PTPN11 specifically in premigratory NCCs. SHP2-deficient NCCs initially exhibited n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 41 publications
(38 reference statements)
1
42
0
Order By: Relevance
“…On the other hand, AS was observed frequently in Sos1 EK/EK mice and in older Sos1 +/EK mice. Finally, in addition to activation of Ras and Erk, we found that Rac and Stat3 were also activated in Sos1 EK mice, which was not found in the Ptpn11 models (38)(39)(40)44). It is possible, if not likely, that the common phenotypes observed in Sos1 and Ptpn11 models, such as growth delay, craniofacial features, hematological disorders, and some cardiac defects, were due to the enhanced Erk activation seen in both models, whereas the distinct features in the Sos1 model described above were due to the selective activation of Rac and/or Stat3.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…On the other hand, AS was observed frequently in Sos1 EK/EK mice and in older Sos1 +/EK mice. Finally, in addition to activation of Ras and Erk, we found that Rac and Stat3 were also activated in Sos1 EK mice, which was not found in the Ptpn11 models (38)(39)(40)44). It is possible, if not likely, that the common phenotypes observed in Sos1 and Ptpn11 models, such as growth delay, craniofacial features, hematological disorders, and some cardiac defects, were due to the enhanced Erk activation seen in both models, whereas the distinct features in the Sos1 model described above were due to the selective activation of Rac and/or Stat3.…”
Section: Discussionmentioning
confidence: 78%
“…Our studies indicate that the phenotypes in Sos1 EK mice and previous NS-associated Ptpn11 D61G or other Ptpn11 mouse models were overlapping to some degree but distinguishable (38)(39)(40)(41)(42)(43). First, Ptpn11 D61G/D61G were completely embryonic lethal, whereas we obtained a small number of Sos1 EK/EK mice (41).…”
Section: Discussionmentioning
confidence: 92%
“…It is not clear whether this finding represents failure of resolution or if it has a different etiology (Maymon et al, 2008). During embryogenesis tyrosine phosphatase (SHP2) deficiency affects neural crest cell function and triggers the events leading to the typical heart and skull anomalies seen, for instance, in Noonan syndrome (NS) fetuses (Nakamura et al, 2009).…”
Section: Common Questions From Parentsmentioning
confidence: 99%
“…SHP2 contributes to higher occurrence of Noonan syndrome disease, a genetic disorder characterizing by defective cardiac and craniofacial developments with estimated prevalence of 1:1000-1:2500 live births. SHP2 plays an essential role for CNC normal migration and differentiation into diverse lineages of the heart and skull (Nakamura et al, 2009). However, the symptoms improve with age and most adults suffering NS do not need special medical care.…”
Section: Human Diseases or Disorders From Defective Neural Crest Pattmentioning
confidence: 99%
“…Ablation of PTPN11 in premigratory neural crest cells, which encodes the protein tyrosine phosphatase (SHP2), contributes to profound skull deficits (Nakamura et al, 2009). A subpopulations of postmigratory CNC have roles in patterning distinct derivatives, such as Hoxa2 (Tavella and Bobola, 2010) acts as a selector gene for patterning of branchial arch structures, and cAMP-dependent protein kinase (protein kinase A (PKA)) has strict regulation on the derivative patterning (Jones et al, 2010).…”
Section: Neural Crest Migrationmentioning
confidence: 99%